IMPLEMENTATION OF PUBLIC PARTICIPATION IN THE ESTABLISHMENT OF RULES OF LAWS AND REGULATIONS IN LEGISLATURE THE HOUSE OF REPRESENTATIVES OF THE REPUBLIC OF INDONESIA DURING THE COVID 19 PANDEMIC - Ikhwanudin, Ikhwanudin; Tuti, Retnowati WD (UNIVERSITAS PAKUAN, 2021)
In the preamble to the Constitution of the Republic of Indonesia, it is stated that one of the objectives of the establishment of the Government of the State of Indonesia is to educate the life of the nation. Educating the nation's life through the education of people's sovereignty is one of the demands of a state of law. Realizing people's sovereignty in the Indonesian constitutional system is implemented through the branches of state power regulated in the Constitution of the Republic of Indonesia. The House Of Representatives (DPR), the Regional Representative Board (DPD), and the President hold the sovereign power of the people respectively. The DPR has the power to make laws. As a branch of state power that has the power to form laws, the DPR must pay attention to the sovereignty of the people which is reflected in the participation of the community or the public in forming laws and regulations, under any conditions, including during the Covid-19 pandemic. The involvement of public participation in legislation is intended so that the legislative products formed by the DPR are in accordance with the principles of people's sovereignty, aspirations and legal needs of the people and carry out the constitutional mandate, namely to educate the life of the nation. The implementation of public participation is not only carried out in the formation of laws and regulations, but also to the supervision of laws, as part of public political education efforts. Thus, one of the objectives of the formation of laws and regulations is to maintain the sovereignty of the people by educating the nation's life, even during the Covid 19 pandemic. This study aims to describe the implementation and objectives of public participation in the formation of legislation in the future. Covid-19 pandemic.